Central and mid-peripheral corneal astigmatism in an elderly population: a retrospective analysis of Scheimpflug topography results - Łabuz, Grzegorz; Vàradi, Dorottya; Khoramnia, Ramin; Auffarth, Gerd U. (Scientific reports, 2021)
Implantation of toric intraocular lenses (IOLs) has become standard in the correction of corneal astigmatism. The IOL selection is based on keratometric measurements of the central cornea. However, mid-peripheral corneal changes may yield suboptimal correction in patients with larger pupils. This study retrospectively analyzed corneal topography data collected using a Scheimpflug device during routine clinical examinations. Of 11,953 patients, 641 met the inclusion criteria. Total corneal astigmatism was compared between five concentric zones (2-6 mm) using vector analysis. The absolute difference between astigmatism at 2 mm and 6 mm was 0.30 D (− 0.36 to 0.64), which decreased to 0.10 D (0 to 0.20) between the 5- and 6-mm zone. With-the-rule astigmatism was the most prevalent (53%), 34% had against-the-rule (ATR), and 13% had oblique. The decrease of the cylinder power with the diameter differed significantly between the three types, with ATR and oblique astigmatism being associated with the steepest change. Patients with high corneal astigmatism tend to demonstrate larger differences between the center and mid-periphery than those with low and moderate astigmatism. In conclusion, we demonstrated that central corneal astigmatism differs from that measured at the mid-periphery and that a larger difference was found in patients with ATR, oblique and high astigmatism.
Gesehen am 11.06.2021